Physiological and Molecular Mechanisms of Methionine Restriction - Latimer, Mary Neslund; Freij, Khalid Walid; Cleveland, Beth M.; Biga, Peggy R. (Frontiers in Endocrinology, 2018)
Methionine Restriction (MR) has been studied extensively over the last 25 years for its role in altering metabolic hallmarks of disease. Animals subjected to MR display changes in metabolic flexibility demonstrated by increases in energy expenditure, glucose tolerance, and lifespan. These changes have been well characterized in a number of model systems and significant progress has been made in understanding how hepatic FGF21 links MR to several components of its metabolic phenotype, despite these advances a complete understanding of mechanisms engaged by dietary MR remains elusive. In this review we offer a brief history of MR and its known mechanisms associated with stress, metabolism and lifespan extension. We consider the role of epigenetics in the response of animals to MR and propose a novel epigenetic pathway involving the regulation of miRNAs during MR.